Steroid diagnostics of 21st century in the light of their new roles and analytical tools - Dušková, Michaela; Kolátorová Sosvorová, Lucie; Šimková, Markéta; Šrámková, Monika; Malíková, Mária; Horáčková, Lenka; Vítků, Jana; Stárka, Luboslav (Physiological research, 2020)
The determination of steroid hormones and subsequent interpretation of results is accompanied by a range of difficulties. The amount of information that current technology can provide on the circulating concentrations of more than a hundred various steroid compounds can lead to problems with interpretation. The aim of this study is to help provide orientation in this maze of data on steroid hormones. First we focus on specific aspects arising from the pre-analytical phase of steroid determination that need to be considered when planning sampling, whether for diagnostics or research. Then, we provide a brief summary of the characteristics and diagnostic relevance of several steroid hormones and/or their metabolites: pregnenolone, 17alpha-hydroxy-pregnenolone, dehydroepiandrosterone, hydroxyderivatives of dehydroepiandrosterone, androstenedione, testosterone, estrone, estradiol, estriol, cortisol, cortisone, which in our institute are determined with validated LC-MS/MS methods. For these steroids, we also provide newly calculated reference values in fertile women according to the phase of their menstrual cycle.
Keywords: Steroids; Hormones; hormony; Diagnostic Tests, Routine; steroidy; diagnostické testy rutinní; lidé; Humans